Application of ultrasound in combination with other methods in gynecological disease: artificial intelligence, surgery, and drugs - Shi, Shaohua; Dai, Chengcheng; Liu, Demin; Liu, Xingjie (Frontiers in Oncology, 2025)
Gynecological diseases (GyD) are related to reproductive tissue disorders such as the cervix, vagina, fallopian tubes, and ovaries, which can affect fertility. Among these diseases, we can mention endometriosis, ovarian laziness, primary ovarian insufficiency, cancers related to these tissues, and even Asherman’s disease. Considering the impact of these diseases on the population’s youth, it is imperative to develop effective methods for diagnosing, treating, monitoring, and preventing their progression. In the past, ultrasound-based methods have been used for early diagnosis of GyD, including ovarian cancer. However, in today’s era, it is essential to enhance the features of this method to ensure that patients are screened more effectively and their treatment responses can be tracked. In recent years, the spread of artificial intelligence has led to its application in various branches of medicine. Many studies have increased their efficiency by combining ultrasound and artificial intelligence methods. Additionally, the simultaneous use of ultrasound and surgery can help improve patient recovery and the success of the procedure. Additionally, various studies have utilized the combination of ultrasound-based methods and different drugs to treat GyD. In this manuscript, we will discuss the pathology of gynecological diseases, the use of ultrasound-based methods, and their combination with other methods.